Candidate Sexual Orientation Didn't Matter (in the Way You Might Think) in the 2015 UK General Election. Issue 3 (25th March 2018) - MAGNI, GABRIELE; REYNOLDS, ANDREW
Abstract : Does sexual orientation and gender identity matter at election time? While previous literature has explored the effect of candidate gender and ethnicity on electoral results, this is the first study to quantitatively investigate the impact of sexual orientation. We build an original dataset combining individual-level data on more than 3, 000 candidates in the 2015 UK election with sociodemographic indicators at the constituency level. In addition to sexual orientation and other demographic characteristics, we include candidate education, political experience, and campaign spending. We find that LGBT candidates generally do not have a negative impact on party vote share. Even in more conservative environments, LGBT candidates perform at least as well as their straight counterparts. This work is important to understand the consequences of descriptive representation and, relatedly, how rapid social change happens.